Advertising expenditure and consumer prices - Rauch, Ferdinand (International journal of industrial organization, 2013)
This paper studies the effect of a change in the marginal costs of advertising on advertising expenditures of firms and on consumer prices. I make use of a policy change in Austria, that involved an increase of the taxation of advertising in parts of the country, and a simultaneous decrease in other parts. I show that advertising expenditures of firms move quickly in the opposite direction of the marginal costs of advertising. Consumer prices increase with advertising in some industries, and decrease in others. This effect correlates with informational differences in advertisements across industries.